2015
DOI: 10.1021/jp507225m
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Surface-Enhanced Infrared Spectroelectrochemistry Studies the Interaction of Cytochrome c with Cardiolipin-Containing Membranes

Abstract: Interactions of cytochrome c (cyt c) with cardiolipin (CL)-containing membranes have been revealed to play an important role in inducing early apoptosis. In this paper, we studied the interaction of cyt c with solid-supported CL-containing lipid bilayers by a lable-free spectroelectrochemistry method. The biomimetic membrane was fabricated by fusing cardiolipin-phosphatidylcholine (CL_PC, 1:4) vesicles onto the hydrophobic surface of a preadsorbed 1-dodecanethiol (DT) on a gold electrode (CL_PC/DT/Au). The ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…Rodes et al monitored the adsorption of glycine on Au thin films using EC-SEIRAS and confirmed that the preferential binding mode is in a bidentate configuration (Figure 7(b)) and that co-adsorption of perchlorate anions from the electrolyte takes place [156]. The application of EC-SEIRAS has further been extended to electrochemical interfaces relevant to biology, recent focus being on the development of model biomimetic structures, enabling the behaviour of transmembrane proteins to be interrogated [158][159][160][161].…”
Section: Electrochemical Infrared Spectroscopymentioning
confidence: 98%
“…Rodes et al monitored the adsorption of glycine on Au thin films using EC-SEIRAS and confirmed that the preferential binding mode is in a bidentate configuration (Figure 7(b)) and that co-adsorption of perchlorate anions from the electrolyte takes place [156]. The application of EC-SEIRAS has further been extended to electrochemical interfaces relevant to biology, recent focus being on the development of model biomimetic structures, enabling the behaviour of transmembrane proteins to be interrogated [158][159][160][161].…”
Section: Electrochemical Infrared Spectroscopymentioning
confidence: 98%
“…[26,29] In Figure 4B proportional to the scan rates up to 100 mV s -1 , consistent with an adsorption-controlled process ( Figure S3B). [32] We also note that the redox potential of cytochrome-c in solution and immobilized onto modified glassy carbon electrode are close (+25 and +12 mV vs.…”
Section: Accepted Manuscriptmentioning
confidence: 61%
“…Different methods can be successfully employed to form supported lipid bilayers including the Langmuir-Blodgett technique, [26] spin coating of lipid solution, [26,29] solvent or droplet evaporation [30,31] or fusion of lipid vesicles at the electrode surface. [32] In most cases, the presence of a fraction of cardiolipin in the supported mixed-lipids bilayer has been demonstrated to be an important factor for the efficient detection of cytochrome-c electroactivity at carbon electrodes. [26,29,31] Indeed most of the lipid films investigated to date were mainly composed of phosphatidylcholine associated with a small fraction of cardiolipin.…”
Section: C E P T E D M a N U S C R I P Tmentioning
confidence: 99%
“…The reference spectra were taken at -0.2 V, where the adsorbed cyt c are fully reduced, while the sample spectra were acquired at successively increased potentials from -0.1 to 0.2 V, where the adsorbed cyt c are gradually until fully oxidized. For cyt c/MUA/Au, the broad water bands at 3450 cm -1 increase in intensity with the sample potential and reach a plateau at 0.1 V. Since the 3450 cm -1 bands in the series of difference spectra of MUA (dotted lines) shows almost no change with the sample potential, ΔI(O-H) (the difference in intensity of the 3450 cm -1 band between cyt c/MUA/Au and MUA/Au), reflects the cyt c redox-induced hydration change of the adsorbed film[38]. The negative nature of the broad water band in the redox-induced difference spectra suggests that the degree of hydration of native cyt c is decreased from the reduced to oxidized state[38].…”
mentioning
confidence: 99%
“…For cyt c/MUA/Au, the broad water bands at 3450 cm -1 increase in intensity with the sample potential and reach a plateau at 0.1 V. Since the 3450 cm -1 bands in the series of difference spectra of MUA (dotted lines) shows almost no change with the sample potential, ΔI(O-H) (the difference in intensity of the 3450 cm -1 band between cyt c/MUA/Au and MUA/Au), reflects the cyt c redox-induced hydration change of the adsorbed film[38]. The negative nature of the broad water band in the redox-induced difference spectra suggests that the degree of hydration of native cyt c is decreased from the reduced to oxidized state[38]. The intensity of ΔI(O-H) divided by the intensity of the 1693 cm -1 vibration (ΔI1693, denoting the coverage of cyt c since the vibration is assigned to the type III β-turns of the protein.…”
mentioning
confidence: 99%